Nutrition knowledge, weight loss practices, and supplement use in senior competition climbers - Gibson-Smith, Edward; Storey, Ryan; Michael, Marisa; Ranchordas, Mayur (Frontiers in Nutrition, 2024)
Sport climbing has gained increased scientific attention, including studies investigating the dietary habits and nutritional requirements of climbers; however, significant gaps in the literature remain. An assessment of nutritional knowledge, weight loss for competition, and supplement use has not been previously reported in senior competition climbing athletes. Fifty climbers (26 male, 24 female; BMI 21.6 ± 1.9; 23.7 ± 5.2 years) participated in the study. Participants answered a 72-item questionnaire, comprised of demographic data and three main sections to assess general and sports nutrition knowledge, weight loss strategies, and supplement use. The mean nutrition knowledge score was 'average', with considerable individual variation (53.5 ± 11.1 %). There were no significant sex differences in the general (GNK) or sport (SNK) nutrition knowledge scores, or effect of age.Significantly higher knowledge was demonstrated by national vs. international athletes for the GNK scores (11.09 ± 1.58 vs. 9.58 ± 1.75; p = 0.028). Participants scored well in questions concerning protein, carbohydrates, alcohol, and supplements, and conversely, performed poorly in hydration and micronutrient related questions. Less than one-fifth of respondents had access to a dietitian. Forty-six percent of males and 38% of female climbers reported intentional weight loss for competition on at least one occasion. Of those, ~76% reported utilising concerning practices, including methods that conform with disordered eating and/or eating disorders, dehydration, vomiting, and misuse of laxatives. Approximately 65% of athletes reported using at least one nutritional supplement in the previous 6 months, with 44% reporting multiple supplement use. There was no significant difference in supplement use between sexes or competition level. Due to the established importance of nutritional intake on athlete health and performance, educational support should be employed to improve knowledge in climbers and address shortcomings. Moreover, intentional weight loss for climbing competition is common, with most athletes achieving ~3-8 % body weight loss over >2 weeks. It is crucial that professionals working with competitive climbers are vigilant in identifying athletes at risk of concerning weight management and establish referral pathways to the appropriate specialist services. High quality intervention trials to assess the efficacy of ergogenic aids in climbing remains inadequate.